Enhancing High School Student Engagement and Academic Achievement: A Comparative Analysis of the JIA Application - Purba, Maria Veronica M; Hasrul, Hasrul (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study compares the effectiveness of the JIA application in enhancing student engagement and learning outcomes in Pancasila Education for Class X students SMA Methodist 02 Palembang. The study employed a quasi-experimental design with a 2x2 format, using non-equivalent groups. Data were collected through observation and multiple-choice tests administered as pretests and posttests. Research sampling was carried out Participants were selected using purposive sampling, purposive sampling type. Data collection was carried out using observation sheets on learning activities and multiple choices formative test questions as pretest and posttest. The JIA application significantly improved student engagement and learning outcomes. The N-Gain Score for learning activities was 46.8%, and for learning results, it was 52.5%. Learning activity increased by 12.70%, from 59.54% to 72.29%. The average learning outcome score improved by 31.02 points, from a pretest score of 47.95 to a posttest score of 78.97. The findings underscore the significant impact of the JIA application in enhancing both student engagement and learning outcomes in Pancasila Education for Class X students at SMA Methodist 02 Palembang. The study's results suggest that integrating technology, such as the JIA application, into educational curricula can substantially elevate student participation and achievement. These findings advocate for the broader implementation of digital tools in educational settings to foster more interactive and effective learning experiences, potentially guiding future policy and curriculum development in schools.